2010
DOI: 10.1177/1477153510377836
|View full text |Cite
|
Sign up to set email alerts
|

Lighting in retail environments: Atmosphere perception in the real world

Abstract: Although ambient lighting and atmosphere are intuitively related, there is a paucity of empirical, naturalistic data supporting such a relation. The objective of this study was to investigate the contribution of lighting in evoking an atmosphere in the real world, amongst the extensive set of other cues available there. In a field study involving 57 clothing stores, lighting attributes (e.g. brightness, contrast, glare and sparkle) and context (i.e. the shop's interior) were assessed and quantified independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 27 publications
2
73
0
9
Order By: Relevance
“…Aqui estão inseridas pesquisas que se propõem a entender como as pessoas percebem e avaliam o espaço, bem como sua relação com o ambiente iluminado, a partir de uma abordagem em termos psicológicos, sociais, subjetivos (Veitch, 2001;Custers et al, 2010).…”
Section: Aspectos Subjetivos Em Iluminaçãounclassified
“…Aqui estão inseridas pesquisas que se propõem a entender como as pessoas percebem e avaliam o espaço, bem como sua relação com o ambiente iluminado, a partir de uma abordagem em termos psicológicos, sociais, subjetivos (Veitch, 2001;Custers et al, 2010).…”
Section: Aspectos Subjetivos Em Iluminaçãounclassified
“…In social sciences, it is used for multivariate statistical problems, for example to reduce the number of variables [13]. In lighting research specifically, PCA is often applied to investigate perception and preference [8], [10], [32]. Wang et al used PCA to study the dimensions of atmosphere perception for dynamic lighting [32].…”
Section: Principal Component Analysismentioning
confidence: 99%
“…In addition, increasing the illuminance (from 40 lx to 400 lx) resulted in a less 'tense', less 'cosy' and more 'lively' atmosphere. Custers et al 25 found a negative relation between brightness and 'cosiness'. From these findings we may conclude that systematic changes in light characteristics influence the atmosphere, and so, the affective experience of the room.…”
Section: Introductionmentioning
confidence: 99%